Advance and Designing Strategies in Polymeric Antifungal Agents Inspired by Membrane‐Active Peptides. Issue 65 (15th September 2022) - Jiang, Weinan; Wu, Yueming; Zhou, Min; Song, Gonghua; Liu, Runhui
Abstract: The high‐mortality invasive fungal infections seriously threaten the lives of immunocompromised people. Host defense peptides and cell‐penetrating peptides are representative membrane‐active peptides with different functions. Among them, host defense peptides mimicking is a valid strategy in the design of synthetic antifungal agents. Despite the brilliance in the field of intracellular delivery, the potential of cell‐penetrating peptides and their mimics for designing antifungal agents has been overlooked. In this concept article, we describe the structural design of synthetic antifungal polymers as mimics of host defense peptides, and highlight the effectiveness and potential of cell‐penetrating peptide‐inspired strategy in designing potent and selective antifungal polymeric agents. In addition, an outlook for further expanding the design horizons of antifungal polymers is also presented. Abstract : The growing prevalence of invasive fungal diseases, the scarcity of existing antifungal drugs, and the continued emergence of antifungal drug resistance urge the development of new antifungal agents. This concept discusses and highlights the advance and designing strategies of antifungal polymeric agents with a focus on design principles inspired by membrane‐active peptides, including host defense peptides and cell‐penetrating peptides.